Similar And Different Aspects In The Texts Of "Mubayyan" And "Hidaya" - Gulruh Kenjaboy Mirzo qizi (Zien Journals, 2024)
This article discusses the harmonious and different aspects of the farce actions cited in Zahiriddin Muhammad Babur's work "Muabayyan" with the work "Hidoya".
Keywords: Farz; salot; niyaz